Becoming a Manager - Hill, Linda (Ascent Audio, 2020)
In your career, there is one transition that stands out as the most crucial-going from individual contributor to competent manager. New managers have to learn how to lead others rather than do the work themselves, to win trust and respect, to motivate, and to strike the right balance between delegation and control. Many fail to make the transition successfully. In this timeless, indispensable book, Harvard Business School professor and leadership guru Linda Hill traces the experiences of nineteen new managers over the course of their first year in the role. She reveals the complexity of the transition, highlighting the expectations of these managers, their subordinates, and their superiors. We hear the new managers describe how they reframed their understanding of their roles and responsibilities, how they learned to build effective cross-functional work relationships, how and when they used individual and organizational resources, and how they learned to cope with the inevitable stresses of leadership. Hill vividly shows that becoming a manager is a profound psychological adjustment-a true transformation-as well as a continuous process of learning from experience. Becoming a Manager, a veritable treasury of essential leadership wisdom, is a book you will turn to again and again no matter where you are on your career journey.